The Importance of Teaching Reading: Emphasize for Reading Fluency or Accuracy in Improving Students’ Reading Comprehension in EFL Context - Muhammad Rochman (Ethical Lingua: Journal of Language Teaching and Literature, 2017)
Current methods for teaching reading comprehension tend to emphasize the products of comprehension and neglect the processes of comprehension. Teachers often provide insufficient opportunities for learners to practice English in teaching reading. To make the situation worse, both teachers and learners frequently use Indonesian language throughout English classes. There are two sets of skills that are particularly important to teach. The first set includes comprehension monitoring skills that involve readers' monitoring their continuing processing for possible comprehension failure and taking remedial action when failures occur. Comprehension failures can occur at various levels, including: particular words, particular sentences, relations between sentences, and relations between larger units. For each kind of failure, there are specific remedial actions readers can take. The second set of processing skills that can be taught involves using clues in the text to generate, evaluate, and revise hypotheses about current and future events in the text. During teaching reading in a class teachers may confuse to give exercises relate to fluency or accuracy. The correlation between fluency and reading comprehension showed a significant positive relationship between oral reading fluency and reading comprehension performance. Therefore, automaticity of decoding fluency is essential for high levels of reading achievement. Hence, what educators should do now is conscientiously try to shift educators’ attention from emphasizing the accuracy of students ‘oral presentation to developing their ability to express themselves both accurately and fluently in English.